Respuestas
Respuesta dada por:
2
P₁ = (1, 5)
P₂ = (3, 1)
Aplicamos la fórmula de la ecuación conocidos dos puntos.
y₂ - y₁
y - y₁ = -------------- (x - x₁)
x₂ - x₁
1 - 5
y - 5 = --------- (x - 1)
3 - 1
- 4
y - 5 = ---------- (x - 1)
2
y - 5 = - 2 (x - 1)
y - 5 = - 2x + 2
2x + y - 5 - 2 = 0
2x + y - 7 = 0
La ecuación es : {2x + y - 7 = 0}
P₂ = (3, 1)
Aplicamos la fórmula de la ecuación conocidos dos puntos.
y₂ - y₁
y - y₁ = -------------- (x - x₁)
x₂ - x₁
1 - 5
y - 5 = --------- (x - 1)
3 - 1
- 4
y - 5 = ---------- (x - 1)
2
y - 5 = - 2 (x - 1)
y - 5 = - 2x + 2
2x + y - 5 - 2 = 0
2x + y - 7 = 0
La ecuación es : {2x + y - 7 = 0}
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años